Aerobic copper-catalyzed homo-coupling of azaallyl anions: A facile access to vicinal diamines. (22nd June 2022) - Shen, Mei-Hua; Guo, Bin; Li, Chen; Sun, Chen-Lei; Zhu, Yi-Fan; Zhu, Chifan; Xu, Hua-Dong; Xu, Defeng
Graphical abstract: Abstract: Agitating a mixture of N-(diphenylmethyl)arylaldimine, t BuOK and catalytic CuCl2 in THF under O2 atmosphere at 75 °C for several hours produces corresponding vicinal diimine. This transformation takes place via a copper-catalyzed oxidative homo-coupling of the in situ generated azaallyl anion, in which molecular oxygen serves as the effective terminal oxidant. 1, 2-diarylethane-1, 2-diamine dihydrochloride is obtained upon hydrolysis with hydrochloric acid.